2015
DOI: 10.1007/978-3-319-21404-7_40
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Cloud Ontology Clustering Mechanism to Enhance IaaS Service Discovery and Selection

Abstract: Abstract. The continuing advances in cloud computing technology, infrastructures, applications, and hybrid cloud have led to provide solutions to challenges in big data and high performance computing applications. The increasing number of cloud service providers offering cloud services with nonuniform descriptions has made it time consuming to find the best match service with the user's requirements.This paper is an effort to speed up the service discovery and selection of IaaS cloud services which is "best-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The mechanism explained in a formal way of service-based method as input parameter and output the functional parameters but the parameter for QoS (Quality of service) is not considered for service selection and composition. Uchibayashi T et al in 14 presented an effective framework for cloud service discovery and selection in a hybrid Cloud Computing environment. For enhancement of the cloud service discovery and selection, they used a heuristic cluster mechanism, however, the methodology for clustering based on the keyword does not consider semantics which may create difficulty in complex and semantic cloud service discovery for the users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mechanism explained in a formal way of service-based method as input parameter and output the functional parameters but the parameter for QoS (Quality of service) is not considered for service selection and composition. Uchibayashi T et al in 14 presented an effective framework for cloud service discovery and selection in a hybrid Cloud Computing environment. For enhancement of the cloud service discovery and selection, they used a heuristic cluster mechanism, however, the methodology for clustering based on the keyword does not consider semantics which may create difficulty in complex and semantic cloud service discovery for the users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As cloud-based services gained prominence among the user groups because of their flexibilities in service provision and infrastructure, a number of cloud service providers came up. Therefore, Uchibayashi et al (2015) observed that the growing number of cloud service providers providing cloud services with non uniform descriptions makes it very difficult for the customer to choose the best compatible service provider matching their needs. In the course of development and magnification of data generation in terms of velocity and volume, the concept of big data is threatening the conventional tools and techniques we use to preserve and process data.…”
Section: Data Magnifications and Cloud Computingmentioning
confidence: 99%
“…In the hybrid model, the semantic relations between services are based on ontology being explored based on a multi-factor system. A model has been proposed on the basis of ontological clustering to explore cloud substructure services [10]. Substructure-based clusters have been created as a service and the ontology of the semantic relations among them has been established.…”
Section: Related Workmentioning
confidence: 99%